A protocol for using rapid qualitative techniques to incorporate multi-level stakeholder feedback in a pragmatic clinical trial of mindfulness for chronic low back pain - Isabel J. Roth; Elondra D. Harr; Christine R. Lathren; Jessica L. Barnhill; Ruth D. Rodriguez; Jose E. Baez; Natalia E. Morone (PLoS ONE, 2026)
Introduction Engaging community members and context experts is increasingly recognized as key to developing research that is responsive to community needs. Here, we describe a protocol for incorporating stakeholder feedback using rapid qualitative techniques into OPTIMUM (Optimizing Pain Treatment In Medical settings Using Mindfulness), a pragmatic clinical trial comparing a telemedicine-delivered mindfulness-based stress reduction intervention to usual care to address chronic low back pain. The aim of this stakeholder feedback supplement to the OPTIMUM parent trial is to consider many viewpoints regarding recruitment, retention, facilitation, delivery, sustainability, and dissemination of this program which are critical to understand before it can be successfully implemented. Methods Our team developed a multi-faceted approach to collecting feedback from representatives of three levels of influence: individuals, communities, and policy. We plan to conduct focus groups with study participants from both the intervention (MBSR) and usual care groups. We plan to conduct one-time semi-structured interviews with a diverse set of people with varied roles and perspectives (e.g., clinic personnel, health care system leadership, mindfulness instructors, patient pain advocacy groups, policy advocates). We will assemble a Community Advisory Board (CAB) to convene regularly throughout the project. Transcripts from interviews, focus groups, and meeting notes will be analyzed using rapid qualitative methods to facilitate timely incorporation of feedback into the trial. In-depth thematic content analysis will be conducted subsequently. Discussion Partnering with communities who are historically underrepresented in clinical research under the guidance of principles such as equity, inclusion, trust, and accountability can improve health outcomes that are most relevant and beneficial to the target community, accelerate uptake, and promote sustainability.